Combretastatin A4‐phosphate and its potential in veterinary oncology: a review. (18th May 2015) - Abma, E.; Daminet, S.; Smets, P.; Ni, Y.; de Rooster, H.
Abstract: For many years, research on anticancer therapy has focussed almost exclusively on targeting cancer cells directly, to selectively kill them or restrict their growth. But limited advances in this strategy have led researchers to shift their attention to other potential targets. Active research is now on‐going on targeting tumour stroma. Vascular disrupting agents (VDAs) appear a promising class of anticancer drugs that are currently under investigation as a sole or combined therapy in human cancer patients. This article will briefly touch on the history and biology of combretastatin A4‐phosphate (CA4P) as a typical example of VDAs and will concentrate on the side effects that can be expected when used in veterinary patients. Particularly, the pathogenesis of these side effects and how they may be prevented and/or treated will be discussed. The purpose of this article is to illustrate the potentials of CA4P as anticancer therapy in veterinary oncology patients.